Crassothonna moniliformis (Asteraceae, Senecioneae), a new species from the Albany Centre of floristic endemism, South Africa - Mckenzie, Robert J.; Dold, Anthony P. (Phytotaxa, 2024)
Crassothonna moniliformis is described as a new species from the Eastern Cape province, South Africa. The species is a prostrate, succulent-leaved perennial herb distinguished from Crassothonna capensis in having slender, weak, trailing, distantly branched stems, with nodal adventitious roots developing precociously, forming diffuse patches to ±50 cm diam., with erect to ascending, usually red-purple, globose-obovoid to obovoid to subclavate leaves 10–25 mm long, and a more slender synflorescence bearing fewer capitula (1–4 per flowering shoot) with fewer ray florets (7–9) and functionally staminate peripheral disc florets. The species is geographically localised, with the known Extent of Occurrence and Area of Occupancy <10 km2, and is habitat-restricted, growing in shallow sandy sediments overlying exposed sandstone pavements among coastal thicket. The single known population is threatened by sand mining and informal housing encroachment. Based on the IUCN Red List categories and criteria, a conservation assessment of Vulnerable (VU – D2) is recommended.